2020
DOI: 10.1088/1757-899x/925/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Operations and Capacity Analysis in India

Abstract: This study highlights the concept of capacity analysis along with traffic operations in urban areas in India. First chapter indicates the introduction of this study through which research aims and objectives can be analysed properly. Moreover, research background and rationale of this study can be also highlighted in this chapter. The second chapter discusses the literature review due to which process of traffic operations and capacity analysis of vehicles can be analysed properly. Using model and theories of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Yigitcanlar et al [16] suggested adopting intelligent transport systems (such as traffic control applications and big data analytics) and smart mobility services to optimize traffic conditions. Reddy and Srivastava [17] reported that traffic operations are considered as one of the important factors for dealing with and managing traffic congestion in urban areas. Alkaissi [18]reported that travel time and delay can be considered as one of the important factors that can be used in evaluating traffic performance in an urban road network.…”
Section: Litreture Reviewmentioning
confidence: 99%
“…Yigitcanlar et al [16] suggested adopting intelligent transport systems (such as traffic control applications and big data analytics) and smart mobility services to optimize traffic conditions. Reddy and Srivastava [17] reported that traffic operations are considered as one of the important factors for dealing with and managing traffic congestion in urban areas. Alkaissi [18]reported that travel time and delay can be considered as one of the important factors that can be used in evaluating traffic performance in an urban road network.…”
Section: Litreture Reviewmentioning
confidence: 99%